Rectovaginal Fistulae - Das, Bidhan; Snyder, Michael (Clinics in Colon and Rectal Surgery, 2016)
Rectovaginal fistulae are abnormal epithelialized connections between the rectum and vagina. Fistulae from the anorectal region to the posterior vagina are truly best characterized as anovaginal or very low rectovaginal fistulae. True rectovaginal fistulae are less common and result from inflammatory bowel disease, trauma, or iatrogenic injury. A very few patients are asymptomatic, but the symptoms of rectovaginal fistula are incredibly distressing and unacceptable. Diagnostic approach, timing, and choice of surgical intervention, including sphincteroplasty, gracilis flaps, Martius flaps, and special circumstances are discussed.
Keywords: anovaginal fistula; rectovaginal fistula; advancement flap; Martius flap; fistula plug